ASSESSMENT OF DENTAL CERAMIC SINTERED AT DIFFERENT TEMPERATURES - Raluca Todor; Emanuela Lidia Crăciunescu; Andreea Codruţa Novac; Alina Doina Tănase; Cosmin Sinescu; Borislav Duşan Caplar; Cristian Zaharia; Daniela Maria Pop; Mihai Romînu; Meda-Lavinia Negruţiu (Romanian Society of Oral Rehabilitation, 2024)
Aim of the Study: The aim of this study is to investigate the modifications that may occur in case of sintering temperature deviation for metal-ceramic crowns. Materials and Methods: For this in vitro study were made 15 metal-ceramic crowns for tooth 2.1 and were divided into 5 groups. The ceramic veneering comprised different sintering temperatures optimized for different properties: group 1 was sintered at 910 ºC as per the manufacturer's recommendation, group 2 was sintered at 940ºC (+30 ºC), group 3 was sintered at 960ºC (+50 ºC), group 4 was sintered at 880ºC (-30 ºC), and group 5 was sintered at 860 ºC (-50 ºC). Using the EXOCAD scanner the maxillary cast was scanned to obtain the metal frameworks from Cr-Co alloy (SCHEFTNER CoCr - 30 microns). Ips InLine One ceramic shade A3 developed by Ivoclar Vivadent Inc is applied in two layers, each one sintered at the same temperature. After ceramic sintering, the shade of each group was registered with Vita Easy Shade spectrophotometer and Vitapan Classical shade guide. Results: Errors in sintering temperatures can change the ceramic's density and mechanical properties but may also lead to colour shifts. This phenomenon occurs due to alterations in the ceramic material's microstructure, which can impact its optical properties and, consequently, its perceived colour. Conclusions: In conclusion, our study highlights the crucial impact of sintering temperature variations on the quality and integrity of metal-ceramic dental restorations. Our findings point towards the need for further innovation and research in thermal management within dental ceramics processing to achieve restorations that are not only aesthetically pleasing but also functionally reliable and compatible with the natural dentition.